Policy Study on Optimizing Family Posyandu Functions to Accelerate Stunting Reduction - Made Darawati; Ni Putu Dian Ayu Anggraeni; Yopi Harwinanda Ardesa; Ridawati Sulaeman; Irianto Irianto; Muh Johansyah (Poltekkes Kemenkes Mataram, 2024)
Background: Based on data from the 2022 Indonesian Nutrition Status Survey (SSGI), the prevalence of stunting in West Nusa Tenggara reached 32.7%. Efforts to overcome stunting using a holistic approach must be carried out, including through the Family Posyandu. Various policies have been issued, one of which is the instruction of the Governor of West Nusa Tenggara No. 050.13/01/KUM of 2022 concerning the Optimization of Family Posyandu to accelerate stunting reduction in West Nusa Tenggara Province, but its implementation has not been widely evaluated. Therefore, it is necessary to study the effectiveness of its implementation to provide constructive suggestions for policymakers.Research Objective: This research aims to identify the implementation of family posyandu, identify factors that influence its success and hinder its implementation, and produce a policy brief related to optimizing family posyandu to accelerate stunting reduction.Research Methods: The research was conducted based on the criteria for an active posyandu, a stunting locus located in the Family Posyandu in the Parampuan Health Center Working Area, West Lombok Regency. Data was collected through Focus Group Discussions (FGD), in-depth interviews, and observations of the implementation of family posyandu.Research Result: The research results show that there needs to be more disclosure regarding foster parents' involvement in optimizing family posyandu to support efforts to accelerate stunting reduction. Several parties' roles involved in implementing family posyandu could be more optimal. Not all targets come to Posyandu, especially teenagers because it is held in the morning when teenagers are at school. Not all family posyandu cadres have received training that meets standards to meet cadre competencies. Monitoring and evaluation of the implementation of family posyandu have yet to be carried out systematically and routinely. Optimizing the role of all parties involved in family posyandu needs to be carried out through increasing the number and capacity of family posyandu cadres on an ongoing basis, massive socialization through various media, systematic and routine monitoring and evaluation accompanied by follow-up efforts, and a well-developed family posyandu information system integrated to be implemented, starting from several pilot family posyandu, so that it can initiate the creation of a village health profile.